1998
DOI: 10.1021/es970492o
|View full text |Cite
|
Sign up to set email alerts
|

Phase Associations and Mobilization of Iron and Trace Elements in Coeur d'Alene Lake, Idaho

Abstract: Sediments of Coeur d'Alene Lake, ID, are heavily contaminated with mine tailings that contain high levels of iron, lead, zinc, arsenic, and other trace elements. These tailings originate from the Silver Valley mining district drained by the South Fork of the Coeur d'Alene River. The possibilities that either lake eutrophication or the develop ment of a seasonally anoxic hypolimnion could mobilize trace elements from sediments into overlying waters led us to evaluate their phase associations. Analysis of ∼0.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
66
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 27 publications
12
66
2
Order By: Relevance
“…In addition to soil contamination, chemical reactions between mine waste and river or lake waters can lead to elevated concentrations of dissolved As (cf. Azcue et al, 1994;Harrington et al, 1998). The maximum contaminant level (MCL) for As in drinking water is under review by the US Environmental Protection Agency.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to soil contamination, chemical reactions between mine waste and river or lake waters can lead to elevated concentrations of dissolved As (cf. Azcue et al, 1994;Harrington et al, 1998). The maximum contaminant level (MCL) for As in drinking water is under review by the US Environmental Protection Agency.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid oxidation of sediment and pore water Fe(II) to Fe(III) hydroxides has been observed by others in this system upon exposure to oxygen after sampling (Horowitz et al 1995b). The anoxic boundary in LCdA has been reported at the water-sediment interface (Harrington et al 1998b), within 5 cm into the sediments (La Force et al 1999;Toevs et al 2006) and between 10 and 15 cm in the sediments (Horowitz et al 1992) and this variability may exist in CdAR as well. As this study focused on sediment cores extracted from the top 15 cm, the majority of the core may have been oxic and thus contained little dissolved Fe.…”
Section: Aqueous Chemistrymentioning
confidence: 92%
“…Horowitz et al (1995a) found that the CdAR and adjacent lake sediments were the most heavily contaminated. Heavy metals in the delta region of LCdA appear to be associated with an operationally defined sulfidic phase (Harrington et al 1998b), while those elsewhere in LCdA appear to be predominantly associated with the more mobile hydroxides (Horowitz et al 1995a;Woods and Beckwith 1997), though there is some controversy on this point (Horowitz et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This process, along with the transport of detrital primary sulfide minerals, could significantly contribute to the transport of metals away from mining areas. In the case of Lake Coeur d'Alene, there has been controversy over whether metals in the sediments are primarily associated with iron oxides (Horowitz et al, 1995(Horowitz et al, , 1999 or a sulfidic phase (Harrington et al, 1998(Harrington et al, , 1999. Recent spectroscopic data point to abundant ferrihydrite and high Fe-to-S ratios in the sediments (Toevs et al, 2006), providing further support that metal transport to the lake could occur primarily as sorbed species onto Fe(III) (hydr)oxides.…”
Section: Introductionmentioning
confidence: 99%